Evidence in treatment of trigger finger: a review - E. R., Ricarte-Almeida; A., Ruiz-Berrones; J., Pérez-Bravo; M., Becerra-Pecero; J. A., Tovar-Ramírez; R. L., Valdés-Ramos; J. I., Mendoza-Argáez; E. M., Jaimes-Durán (International Surgery Journal, 2023)
Sclerosing flexor tenosynovitis (commonly known as “trigger finger”) is one of the main causes of pain and disability in the hand for which patients attend reconstructive and orthopedic surgery. The pathophysiology of this affectation is based on the presence of repetitive trauma that generates an inflammatory process in the sheath of the flexor tendon of the fingers, which eventually generates an alteration in the hand pulley system and produces all the manifestations characteristics of this disease. First and second author independently searched databases using the following databases: Medline, Cinhal, Pubmed, Cochrane Library, and Clinicaltrials.gov, using the keywords: trigger finger conservative and surgical management. Publications that evaluated the effectiveness and provided comparative and conclusive information on the results of surgical and conservative management for carrying out this work were reviewed and considered. The usefulness of 3 therapeutic methods for managing trigger finger was reviewed, identifying a success rate of 56% with isolated steroid injection and up to 79.6% when used serially; in the use of orthoses, a reduction in the symptom score was identified in all cases, although there is no conclusive evidence on long-term results and complete resolution of the condition; Regarding surgical treatment, it was determined that it represents the best alternative for long-term symptom resolution, with a higher rate of sequelae such as pain within the first week or nerve injury. Intrafascial steroid-based injection represents the initial technique of choice in the management of trigger finger. The use of orthoses may represent an alternative in patients who have no impediment for their use for a fairly long time. Open surgical treatment continues being the therapeutic measure to be overcome, with a high symptom resolution rate 1 year after the procedure.